The Translation of Idiomatic Expressions: A Case Study of “Ikan-Ikan Yang Terdampar” Translated into “Stranded Fish” - Tasumbey, Ririn (Institut Agama Islam Negeri Parepare, 2025)
Idiomatic expressions are an essential aspect of language and often pose significant challenges in translation due to their strong cultural underpinnings. This study examines the translation of idioms in the short story “Ikan-Ikan yang Terdampar”, which has been translated into “Stranded Fish”. A qualitative method is employed, supported by Newmark’s Semantic and Communicative Translation Theory. The analysis reveals instances of translation loss, gain, and skewing, highlighting the complexities involved in translating culturally bound expressions. The findings underscore the importance for translators to consider cultural context in order to retain the idiomatic meaning and avoid misinterpretation or distortion during the translation process.